"How Godfather Part II of You": The Gangster Figure and Transnational Masculinities in Marlon James's A Brief History of Seven Killings. Issue 1 (2nd January 2020) - Evans, Lucy
Abstract : Set in Kingston, New York and Miami in the 1970s, 1980s and 1990s, James's novel A Brief History of Seven Killings charts the transformation of politically affiliated Jamaican gangs into transnational criminal organizations. The novel references various incarnations of the "gangster" in the context of mid- to late-twentieth-century Jamaica: the rudie, the shotta and the don. In this essay I consider how, through its engagement with the iconography surrounding the gangster figure both within Jamaican popular culture and in the global mass media, A Brief History examines and complicates models of masculinity associated with this figure. In the process, I suggest, the novel at once reflects on and contributes to evolving Jamaican and transnational discourses of masculinity. Reading A Brief History as a gangster narrative, I position it within an increasingly global tradition of gangster fiction and film. The novel's multiple narrative voices and perspectives, along with its eclectic range of cultural reference points, render the gangster icon – a central component of the genre – ambiguous and plural. I argue that through his reworking of the gangster figure, James both queers the gangster genre and extends its transnational reach.